Program Intervensi Musik terhadap Hiperaktivitas Anak Attention Deficit Hyperactivity Disorder (ADHD) - Bestari Nindya Suyanto; Supra Wimbarti (Faculty of Psychology, Universitas Gadjah Mada, 2019)
Children with hyperactivity subtype of ADHD have difficulty to control their behavior, therefore early intervention is needed by providing therapy specifically designed for children with ADHD. The music intervention program was structured to reduce hyperactivity in children with ADHD. The method of this study was a single case experimental design, the study did not have a control group. The participant in this study was a child with hyperactivity subtype of ADHD who never received music therapy. The measurement of hyperactive behavior was done using a behavioral checklist. Data were analyzed using inter-observer by visual inspection. The results of this study were music intervention could reduce hyperactive behavior in these participants. The reliability of measurements (IOA) was in the range of 80% -100%, meaning that there was a level of trust in the consistency of the assessment between observers in the good category.